Evaluating Security Risks and the Impact of Analytic Technology on the Audit Process - Sutisna, Entis (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to evaluate the impact of analytic technology on the audit process in the digital age, with a particular focus on emerging security risks. The research investigates how technologies such as Big Data Analytics (BDA), Audit Data Analytics (ADA), and Artificial Intelligence (AI) enhance audit efficiency while addressing associated security vulnerabilities. Research Design and Methodology: The study employs a systematic literature review (SLR) methodology to synthesize existing empirical and theoretical insights related to digital audit technologies and security risks. By reviewing academic articles, case studies, and industry reports, the research provides a comprehensive understanding of the current landscape of digital audits. Findings and Discussion: The findings reveal that analytic technologies significantly enhance the accuracy and efficiency of audits by enabling real-time data analysis and predictive insights. However, adopting these technologies introduces new security risks, such as cyberattacks, data breaches, and algorithmic biases. The research also highlights the need for robust data governance, auditor training, and regulatory adaptation to ensure these technologies contribute to secure and transparent audit processes. Implications: The study provides valuable implications for both practice and policy. It emphasizes the need for organizations to integrate advanced technologies while safeguarding audit integrity and security. The study calls for enhanced data governance, continuous auditor training, and the revision of audit standards to accommodate the evolving digital landscape, ensuring that technology adoption does not compromise audit quality.